Effect of carbon material composition on the energy consumption in 22.5 MVA silicon furnace. (14th October 2022) - Chen, Zhengjie; Zhang, Hongmei; Ma, Wenhui; Wu, Jijun
Abstract: The influence of various process parameters during silicon production in a 22.5 MVA submerged arc furnace (SAF) was studied to achieve energy-saving effects. This paper analyzed how the main impurities (Fe2 O3, Al2 O3, CaO) in the main components (fixed carbon, ash, volatile matter, and moisture) of the raw materials used during industrial silicon smelting affected the process using correlation coefficients and contour maps. The results showed that the effect of the main components of the raw materials in a large-capacity furnace was fixed carbon > volatile content > moisture. The effects were significantly reduced compared with a 12.5 MVA. Under the same fixed carbon ratio, coal was more conducive to silicon production than petroleum coke, and the large-capacity furnace had a higher effective utilization rate of raw materials. The falls into order of the influence of metal oxide content on power consumption was Fe2 O3 >Al2 O3 >CaO. Graphical Abstract: UF0001